Dampak Perubahan Iklim Terhadap Ketahanan Bisnis Di Sektor Pertanian Dan Perdagangan - Hendri (CV. SINAR HOWUHOWU, 2025)
Climate change poses a significant challenge impacting various economic sectors, particularly agriculture and trade. This study aims to analyze the effects of climate change on business resilience in these two sectors and to identify adaptation strategies employed by business actors. A qualitative research method was used, involving in-depth interviews, field observations, and document analysis with business actors in climate-vulnerable areas. The findings indicate that climate change causes significant disruptions in agricultural production and trade distribution, resulting in uncertainty and economic losses. Nevertheless, adaptation strategies such as product diversification, the use of climate-resilient technologies, and supply chain management innovations have helped enhance business resilience. The main constraints identified include limited access to technology, information, and capital. This study recommends strengthening collaboration among government, private sector, and communities, as well as utilizing information technology to improve business preparedness against climate risks. These findings are expected to inform the development of more effective policies and adaptation strategies in response to climate change.